A new perspective on the regulation of glucose and cholesterol transport by mitochondria-lysosome contact sites - Chen, Xiaolong; Li, Chun Guang; Zhou, Xian; Zhu, Minghua; Jin, Jing; Wang, Ping (Frontiers in Physiology, 2024)
Mitochondria and lysosomes play a very important role in maintaining cellular homeostasis, and the dysfunction of these organelles is closely related to many diseases. Recent studies have revealed direct interactions between mitochondria and lysosomes, forming mitochondria-lysosome contact sites that regulate organelle network dynamics and mediate the transport of metabolites between them. Impaired function of these contact sites is not only linked to physiological processes such as glucose and cholesterol transport but also closely related to the pathological processes of metabolic diseases. Here, we highlight the recent progress in understanding the mitochondria-lysosome contact sites, elucidate their role in regulating metabolic homeostasis, and explore the potential implications of this pathway in metabolic disorders.